1983
DOI: 10.1161/01.hyp.5.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex sensitivity modulates vasodepressor response to nitroprusside.

Abstract: SUMMARY Baroreflex activity is a determinant of the homeostatic response to alteration in blood pressure. We examined the factors that determine the magnitude of the vasodepressor response to sequential incremental intravenous infusions of sodium nitroprusside (NP), 0.05 to 6.4 yug/kg/min, in eight male patients with essential hypertension. Each infusion level was of 10 minutes' duration. Change from control values of mean arterial pressure (AMAP), heart rate (AHR) and plasma norepinephrine (ANE) were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…1,[3][4][5][6][7]9,14,16,[18][19][20][21]27,31 The baroreflex sensitivity is different for blood pressure increases and reductions, which is evident by comparing phenylephrine with nitroprusside infusion, or neck pressure with neck suction methods. [18][19][20] Heart rate asymmetry, although independent of blood pressure asymmetry, is probably related to baroreflex, which is supported by the observation that heart rate asymmetry is correlated with measures of baroreflex function. 32 Porta et al 33 showed that asymmetrical features of HRV change during sympathetic provocation like head-up tilting and that heart rate asymmetry expression increases during the day compared with night, both in healthy people and patients with congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,[3][4][5][6][7]9,14,16,[18][19][20][21]27,31 The baroreflex sensitivity is different for blood pressure increases and reductions, which is evident by comparing phenylephrine with nitroprusside infusion, or neck pressure with neck suction methods. [18][19][20] Heart rate asymmetry, although independent of blood pressure asymmetry, is probably related to baroreflex, which is supported by the observation that heart rate asymmetry is correlated with measures of baroreflex function. 32 Porta et al 33 showed that asymmetrical features of HRV change during sympathetic provocation like head-up tilting and that heart rate asymmetry expression increases during the day compared with night, both in healthy people and patients with congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most physiological and clinical studies continuous noninvasive recordings of blood pressure signal at the finger level are most commonly used. [4][5][6][7][8][9]14,[18][19][20][21]27,35 Studies on blood pressure asymmetry can develop in different directions. First, the explanation of the mechanisms responsible for this phenomenon like the influence of respiration, autonomic provocations or blockade is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baroreflex sensitivity was calculated by linear regression analysis of AHR versus AMAP during a nitroprusside infusion test, 25 and significant linear correlations were noted in each subject before and during 2.74±0.80t MAP = mean arterial pressure; HR = heart rate; NE = plasma norepinephrine concentration; EPI = plasma epinephrine concentration; PRA = plasma renin activity; ANG I = angiotensin I.…”
Section: Resting Supine Hemodynamic and Neuroendocrine Measurements Dmentioning
confidence: 99%
“…25 By relating changes in HR (AHR) to the changes in MAP (AMAP) during the infusion of each dose of sodium nitroprusside, baroreflex sensitivity was calculated. In addition, the responsiveness of the sympathetic nervous system was assessed by relating the changes in plasma norepinephrine concentration (ANE) to AMAP.…”
mentioning
confidence: 99%